Determinants of Asset Ownership Among Households in Abak Local Government Area, Akwa Ibom State, Nigeria - Victoria Nkan; Blessing Thomas; Ngozi Nwonye (International Journal of Home Economics, Hospitality and Allied Research)
The Feminist Economic Theory posits that traditional economic models often overlook or misrepresent the contributions and constraints faced by different genders in household resource allocation and wealth accumulation. This framework helps in analyzing how patriarchal norms, cultural practices, and socio-economic policies contribute to the observed gendered patterns of asset ownership. Thus, this study examines the determinants of asset ownership among households in Abak Local Government Area, Akwa Ibom State, Nigeria, focusing on gender disparities and socioeconomic factors influencing wealth accumulation. Employing a mixed-methods approach, data were gathered from 400 respondents using structured questionnaires and analyzed with descriptive and inferential statistics. Findings reveal significant gender disparities in asset ownership; men predominantly own land (73.3%), buildings (88.3%), and cars (86%), while women lead in business ownership (68.3%). Key determinants identified include the decision-making power of family heads (mean score = 1.35), cultural traditions (mean score = 1.25), and marital status (mean score = 1.21). A T-test confirmed a significant gender gap, with men owning an average of 6.49 assets versus 3.19 for women (t-value = 20.5, p < 0.05). The study emphasizes the necessity for targeted interventions, including legal reforms, financial inclusion programs, and educational initiatives, to address gender inequality and promote equitable asset distribution. These results contribute to the discourse on wealth inequality and offer policy recommendations for fostering inclusive economic growth and poverty alleviation, ultimately aiming to inform policies that bridge the gender asset gap and enhance economic security for all households.